Analysis of the Impact of Bitcoin Mining Ecosystem Growth on Global Electricity Consumption 2018-2022 - Aminata, Jaka; Ismiyati, Ismiyati (Al-Makki Publisher, 2025)
This study examines the relationship between the Bitcoin mining ecosystem and global primary electricity consumption using variables such as hashrate, Bitcoin market value, mining difficulty, adjusted transaction value, and the number of Bitcoin transactions. A quantitative method is employed, utilizing Vector Error Correction Model (VECM) analysis with E-Views 12. Granger causality analysis reveals a relationship between the number of Bitcoin transactions and hashrate, as well as between Bitcoin market value and Bitcoin transactions. Long-term findings show that Bitcoin hashrate and market value significantly increase global primary electricity consumption, while mining difficulty, adjusted transaction value, and transaction number do not. However, in the short term, mining difficulty and transaction number positively impact energy consumption, while transaction number alone does not have a significant effect.